IoT Monitoring System for Vending Machine - Nisaa Yasmin bt Nor Izuddin; Huda bin A Majid (Progress in Engineering Application and Technology, 2021)
This project is to develop an IoT Monitoring System for Vending Machine which could solve the problem of vending machine owners having to manually go to the vending machine and check the stocks. A prototype of wireless remote access for the vending machine was made by using a few components and the Blynk app on the phone to develop an IoT monitoring system for the status and availability of product which also provides an end user platform. The prototype consists of two parts, the dummy VMC and also a NodeMCU connected to the WiFi network. The prototype works when the dummy VMC displays the number of stocks on the display attached and the Blynk app displaying the same number on the dummy VMC. This project is to help vending machine owners in restocking by reducing the cost of transportation and manpower to restock the items. By developing this project and implementing IoT, the interest of the audience in the electronic industry in the vending machine area will be enhanced. This project report will fully provide the complete information and progress on how the IoT monitoring system for vending machine is made.